From Craftsmanship to Connectivity: Exploring Networked Learning in a Contemporary Corporate Apprenticeship Program in the United States - Forshaw, Tessa (Proceedings of the International Conference on Networked Learning, 2024)
Apprenticeship is a long-valued form of workforce learning. Historical models of craft apprentices learning a trade from a master have prevailed for centuries. In more recent eras, apprenticeship programs have proliferated in industrial sectors and are now facing a revival in corporate settings (Fuller & Sigelman, 2017; Federal Reserve Bank, 2019). However, corporate programs today face different challenges than earlier renditions. Specifically, programs today must enable learning outcomes in a digital context, as professional work today increasingly involves digital or hybrid working environments. Much of the existing literature on apprenticeship focuses on the nature of the craft apprenticeship or the specific features of cognitive apprenticeship within a developmental relationship. Given the rapidly growing number of modern corporate apprenticeship programs, it is essential to understand how learning happens in these dynamic environments. This paper analyzes interview data and five participant case studies to examine a modern corporate apprenticeship program at a multinational consulting firm. The program is a full-time and fully paid learning and working experience for non-degree candidates. It operates in 40 cities across the United States and has enrolled over 2,000 apprentices. Apprentices have formal and informal learning experiences throughout the program, including on-the-job learning. They also work in geographically dispersed teams via a hybrid workplace that is predominantly virtual. Emic themes reveal that digital tools afford apprentices access to a broader networking environment, level up independently, engage in informal betterment with experienced others, and participate in shared discovery and problem-solving with peers. However, situated learning in a project context and strong relationships with various experienced others are equally essential to the digital tools. Drawing upon epistemic lenses of learning that consider how technologies enable learning across multiple activities, environments, and relationships, these findings paint a picture of how apprentices collaboratively engage in value-generating activities as mediated by technology and engage in networked learning.